Independent and combined effects of fine particulate matter and greenness on autism spectrum disorder symptoms: investigating sensitive periods of exposure in the early two years of life - Liu, Yi; Zhou, Wensu; Liu, Meng; Wang, Yichao; Chen, Shu; Xiong, Xiyue (Frontiers in Pediatrics, 2025)
BackgroundThe impact of exposure to fine particulate matter (aerodynamic diameter ≤2.5 μm, PM2.5) and greenness during early two year of life on Autism Spectrum Disorder (ASD) symptoms, especially under the combined influence of the two factors, and the sensitive periods of exposure during the early life, remain underexplored.ObjectiveThis cross-sectional study recruited 108 children with ASD and aimed to quantify the independent and combined effects of PM2.5 and greenness exposure on ASD symptoms during the first two years of life.MethodsWe collected PM2.5 levels and Normalized Difference Vegetation Index (NDVI) values to reflect PM2.5 exposure and greenness levels, meanwhile, assessing ASD symptoms with the Autism Behavior Checklist (ABC) and its sub-scales (sensory, relating, stereotypic behavior, language, and social independence) scores. We identified six sensitive exposure periods: 6 months, 7–12 months, 13–18 months, 19–24 months after birth, and the first and second years after birth. We investigated the independent effects of PM2.5 and greenness on ASD symptoms using multiple linear or logistic regression for continuous or categorical symptom scores, and explored their additive interaction and mediation effects.ResultsMultiple linear models showed reduced total ABC, relating, and social independence scores with greenness exposure at 19–24 months after birth, while 7–12 months and first year exposures benefited social independence. Logistic models showed that PM2.5 exposures during 13–18 months after birth increased symptoms of stereotypic behavior, while low greenness exposure during 19–24 months after birth heightened the risk of social independence impairment. We found high levels of PM2.5 and low greenness during the 13–18 months after birth increased the risk of overall severity. Greenness exposure during 6 months after birth could mitigate the effects of PM2.5 exposures during 13–18 months.ConclusionOur findings underscore the importance of reducing air pollution and enhancing greenness to mitigate ASD symptoms.